Investigation of Optical Communication Systems Used in Different Media - Kose, Abdullah Huzeyfe; Unverdi, N. Ozlem (IEEE, 2022)
In this study, different optical communication media have been designed, and the results of the transmission lines have been observed. The effects of the type of the modulator, power of laser, frequency of the source and the length of the optical transmission line on the data transmission quality were examined with the OptiSystem 18.1 simulation program.
Keywords: Communication technologies; optical communications; optical fiber; free space optical communications; optical wireless communications; Computer Science; Engineering; Telecommunications